Yoga on Our Minds: A Systematic Review of Yoga for Neuropsychiatric Disorders - Balasubramaniam, Meera; Telles, Shirley; Doraiswamy, P. Murali (Frontiers in Psychiatry, 2013)
Background: The demand for clinically efficacious, safe, patient acceptable and cost-effective forms of treatment for mental illness is growing. Several studies have demonstrated benefit from yoga in specific psychiatric symptoms and a general sense of well-being. Objective: To systematically examine the evidence for efficacy of yoga in the treatment of selected major psychiatric disorders. Methods: Electronic searches of The Cochrane Central Register of Controlled Trials (CENTRAL) and the standard bibliographic databases, MEDLINE, EMBASE and PsycINFO, were performed through April 2011 and an updated in June 2011 using the keywords yoga AND psychiatry OR depression OR anxiety OR schizophrenia OR cognition OR memory OR attention AND randomized controlled trial. Studies with yoga as the independent variable and one of the above mentioned terms as the dependent variable were included and exclusion criteria were applied. Results: The search yielded a total of 124 trials, of which 16 met rigorous criteria for the final review. Grade B evidence supporting a potential acute benefit for yoga exists in depression (4 RCTs), as an adjunct to pharmacotherapy in schizophrenia (3 RCTs), in children with ADHD (2 RCTs) and Grade C evidence in sleep complaints (3 RCTs). RCTs in cognitive disorders and eating disorders yielded conflicting results. No studies looked at primary prevention, relapse prevention or comparative effectiveness versus pharmacotherapy. Conclusions: There is emerging evidence from randomized trials to support popular beliefs about yoga for depression, sleep disorders, and as an augmentation therapy. Limitations of literature include inability to do double-blind studies, multiplicity of comparisons within small studies and lack of replication. Biomarker and neuroimaging studies, those comparing yoga with standard pharmaco- and psychotherapies, and studies of long-term efficacy are needed to fully translate the promise of yoga for enhancing mental health.